2022
DOI: 10.3389/fpls.2022.1048814
|View full text |Cite
|
Sign up to set email alerts
|

Pomelo seed oil: Natural insecticide against cowpea aphid

Abstract: Cowpea aphid (Aphis craccivora Koch) is a plant pest that causes serious damage to vegetable crops. Extensive use of synthetic chemical pesticides causes deleterious effects on consumers as well as the environment. Hence, the search for environmentally friendly insecticides in the management of cowpea aphids is required. The present work aims to investigate the aphicidal activity of pomelo seed oil (PSO) on cowpea aphids, the possible insecticidal mechanisms, its chemical constituent profile, as well as the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The AChE could catalyze the hydrolysis of acetylcholine to stop nerve impulses as an essential hydrolase for normal signal transduction of insects. 45 The unchanged AChE activity indicated that compounds 1 and 13 did not act as nerve poisons. Chitinase plays various roles in insects, such as turnover of cuticular chitin, immune defense, increasing potency of venom, and baculo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AChE could catalyze the hydrolysis of acetylcholine to stop nerve impulses as an essential hydrolase for normal signal transduction of insects. 45 The unchanged AChE activity indicated that compounds 1 and 13 did not act as nerve poisons. Chitinase plays various roles in insects, such as turnover of cuticular chitin, immune defense, increasing potency of venom, and baculo.…”
Section: Discussionmentioning
confidence: 99%
“…The GST and CarE could activate the detoxification system and alleviate the toxicity symptoms of insects as important detoxification enzymes. , The CarE participated energetically in the resistance of pyrethroid and organophosphorus insecticides in various pest species. In this study, CarE gained enhanced detoxification ability because of compound 1 , which further suggested that CarE was connected to the detoxification metabolism of 1 . The AChE could catalyze the hydrolysis of acetylcholine to stop nerve impulses as an essential hydrolase for normal signal transduction of insects . The unchanged AChE activity indicated that compounds 1 and 13 did not act as nerve poisons.…”
Section: Discussionmentioning
confidence: 99%